Pemberdayaan Komunitas Basis Gerejawi (KBG) dengan Pendekatan Appreciative Inquiry (AI) - Rexi Alfrids Baptista Kawuwung (Jurnal Seri Mitra (Refleksi Ilmiah Pastoral), 2022)
A primary and real community within the Church that originates from the laity is known as the Basic Ecclesial Community (BEC). Each BEC has its own qualities and distinctiveness as a basic or grassroots community, both in togetherness and diversity. Togetherness and similarity become the defining characteristics of the communio, where members not only "exist" as a group but also learn to recognize and become adjacent to one another. BEC as a collective of individuals appears to play a critical role in the growth of the lay community as a whole. The issue that frequently occurs is that the BEC is stalled or obstructed, which hinders communio, participatio, and missio in its implementation. In this article, an Appreciative Inquiry (AI) approach is used to provide a way to intensify BECs. According to the author, BEC can be fostered by using AI as an effective organizational strategy. AI is a tool for simultaneously developing and nurturing BEC, which might boost the participation and empowering laities on their daily basis.